Patent Foramen Ovale and Closure Technique with the Amplatzer Occluder - Bernhard Meier (Scientifica)
Proof that percutaneous closure of the patent foramen ovale (PFO) is superior to medical treatment is still incomplete. Paradoxical embolism is a rare event occurring over decades rather than years. None of the 4 randomized trials published carried enough patients or was followed up for long enough to reach superiority endpoints. All data, however, point to a benefit of PFO closure. Free wall erosion (exceedingly rare) and triggering of atrial fibrillation (in about 1% of patients) are the only noteworthy complications. They are outweighed by the supposedly prevented events of paradoxical embolisms, such as stroke, transient ischemic attacks, myocardial infarctions, or other systemic embolisms. Medical treatment with perhaps the exception of lifelong oral anticoagulation provides less protection. During a 10-year follow-up of a comparative study the annual mortality was significantly lower in the patients with PFO closure (0.4%) than in those with medical treatment (1.1%, P<0.03). PFO closure can be accomplished in less than 1 hour with immediate resumption of physical activity. It represents thus a kind of mechanical vaccination.